IMPLEMENTASI ENKRIPSI FILE BERBASIS CRYPTOGRAPHY UNTUK KEAMANAN DATA DI WINDOWS 10 MENGGUNAKAN ALGORITMA (AES) - Rohman, Ali; Munawir, Ahmad (Jurnal Ilmiah Sistem Informasi, 2023)
This research aims to develop and implement a file encryption method based on the cryptography library in Windows 10 to enhance data security. The encryption uses the Advanced Encryption Standard (AES) algorithm with a 256-bit key in Galois/Counter Mode (GCM), known for its high security. The encryption key is generated using the Scrypt algorithm, ensuring resistance to brute-force attacks. The implementation includes file encryption and decryption with secure handling of salt, initialization vector (IV), and authentication tag. The research results show that this method is effective and efficient in protecting data from unauthorized access in the Windows 10 environment. In conclusion, the use of AES-256-GCM with the cryptography library provides a robust and reliable solution for data security, which is expected to serve as a reference in the development of information security technology